AGE-RELATED ASPECTS OF MALE FACIAL SKIN STRUCTURE - Shepitko, V.I.; Yeroshenko, G.A.; Lisachenko, O.D. (World of Medicine and Biology, 2013)
The age-related changes of skin and their correction are the important problem of modern dermatology and cosmetology. New methodologies of fight appear and improve against aging of skin. Methods of correction of aging of skin must be complex and to depend on the dominant type of aging, concomitant diseases, age, type of skin and motivations of patients.
Keywords: skin; age-related changes; aging of organism